Combining ability analysis for true seed crop in potato (Solanum tuberosum) - GOPAL, J (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1992-95 on 72 crosses from 18 x 4 factorial mating design to evaluale them for 10characters in seedling (transplanted) and seedling.tuber potato crops. Both additive and non-additive gene actions werefound to be important with a preponderance of the later in the inheritance of various characters. All types of epistaticgene actions were important to specific combining ability. Progeny means of crosses involving both or at least one parentwith good general combining ability were, in general, higher than other cross combinations for various characters includingtuber yield. Selection of parents based on their general combining ability and crossing them in all possiblecombinations to select the best/a few top crosses by progeny test would be a suitable breeding strategy for true potatoseed crop. Superior parents and crosses were identified.